Are the determinants of young SME profitability different? Empirical evidence using dynamic estimators - Nunes, Paulo Maçãs; Viveiros, Ana; Serrasqueiro, Zélia (Journal of Business Economics and Management, 2012)
Using two step method, namely probit regressions and dynamic estimators, and on the basis of two sub-samples of Portuguese SMEs: 1) 495 young SMEs; and 2) 1350 old SMEs, this study seeks to verify if age is a important factor of the relationships between determinants and profitability. Age, size, liquidity and long-term debt are of greater relative importance for the increased profitability, while risk is of greater relative importance for diminished profitability of young SMEs, compared to the case of old SMEs. R&D expenditure is of greater relative importance for increased profitability in old SMEs. Additionally, old SMEs have more persistent profitability than do young SMEs.